2003
DOI: 10.1002/jmv.10334
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of human‐viral DNA junctions in hepatocellular carcinoma from patients with HCV and occult HBV infection

Abstract: DNA of free hepatitis B viruses (HBV) has been detected in the liver of patients infected with hepatitis C virus (HCV). It is unknown whether HBV DNA is integrated into such livers; if so, it may affect hepatocarcinogenesis. Hepatocellular carcinomas (HCCs) from 34 patients without HBV surface antigen (HBsAg) and with anti-HCV, and from 7 patients with HBsAg and without anti-HCV as controls, were examined, using the cassette-ligation-mediated polymerase chain reaction and primers based on HBV DNA sequence. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 24 publications
2
38
0
1
Order By: Relevance
“…The prevalence of occult infection seems to be closely related to the prevalence of HBV infection in different parts of the world. Several investigators have shown an intermediate to high occurrence of HBV occult infection, both in serum and in liver tissue (1,2,4,(8)(9)(10)(11)(12)(13)(14)(15). In Brazil, particularly in the Southeast region, the prevalence of HBV infection is very low (21) and this may have contributed to our results of an HBV occult infection rate close to zero.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The prevalence of occult infection seems to be closely related to the prevalence of HBV infection in different parts of the world. Several investigators have shown an intermediate to high occurrence of HBV occult infection, both in serum and in liver tissue (1,2,4,(8)(9)(10)(11)(12)(13)(14)(15). In Brazil, particularly in the Southeast region, the prevalence of HBV infection is very low (21) and this may have contributed to our results of an HBV occult infection rate close to zero.…”
Section: Discussionmentioning
confidence: 58%
“…Cirrhosis is considered to be the most important risk factor for HCC. Therefore, besides having a possible direct oncogenetic effect, occult HBV infection may increase neoplastic transformation in HCV-infected patients (4,8). The oncogenicity of occult HBV infection is related to the transactivating role of the HBx protein and to the ability of HBV to integrate the host genome (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18] Futhermore, HBV has been detected in the hepatic tissue of some patients after Tumor-free survival rates after liver resection for hepatocellular carcinoma. Circles, 58 patients whose sera were positive for hepatitis B surface antigen but negative for antihepatitis C virus antibody (group A).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a direct examination using cassette-ligation-mediated PCR in the junctions between HBV DNA and human DNA, the integration of HBV DNA was identified in 10 out of 34 HCC patients, all of whom were OHB positive. Four of these integrations were observed in chromosome 11q (78). Altogether, clear evidence exists that OHB infection HBV maintains its pro-oncogenic properties in case of occult HBV infection, possibly by integrating with the host genome, the synthesis of pro-oncogenic proteins by free intra-hepatic HBV genomes (33, 36, 47, 52, 64, 69), or by progression from through cirrhosis to hepatocellular carcinoma (73).…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%